Serum uric acid and cardio-renal diseases. (April 2013) - Ruilope, L.M.; Pontremoli, R.
Abstract Objectives: In this article, the results of clinical and experimental studies that examine the association of hyperuricemia and gout with hypertension and kidney disease are presented and discussed. Methods: Key papers for inclusion were identified by a PubMed search, and articles were selected according to their relevance for the topic, according to the authors' judgment. Results and conclusions: Increasing evidence supports a causal role for Uric acid (UA) in hypertension. Further larger studies are needed to confirm the possible beneficial role of UA lowering drugs and/or xantine-oxidase (XO) inhibitors. Overall, clinical evidence suggests a relationship of UA level with incident chronic kidney disease (CKD). In addition, the results of clinical trials using urate lowering therapy provide some promising evidence that lowering UA levels may retard the progression of CKD. Reviewed data indicate the need for large, well designed studies in these patients to evaluate XO inhibitors or uricosuric drugs in cardio-renal diseases and further elucidate the role of UA in the development and progression of CKD.